2009
DOI: 10.1177/0887403409346110
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Situational Crime Prevention Strategies Across Convenience Stores and Fast-Food Restaurants

Abstract: Although the efficacy of situational crime prevention (SCP) strategies on convenience store safety has received considerable attention, the security of fast-food restaurants has been virtually ignored. This study was based on a population of convenience stores (n = 295) and fast-food restaurants (n = 321) in Charlotte, North Carolina. The study examined whether the crime control strategies commonly recommended to the convenience store industry were effective at reducing robbery in the fastfood industry. Relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…With regard to the former, many studies have found that convenience stores attract armed robbers who are looking to rob a cashier for the money in the register (D’Alessio & StolzenBerg, 1990; Duffala, 1976; Exum, Kuhns, Koch, & Johnson, 2010). These studies have identified which types of stores pose the highest risk of victimization based on store accessibility and contextual factors so that crime prevention measures can be implemented.…”
Section: Commercial Facilities and Crimementioning
confidence: 99%
“…With regard to the former, many studies have found that convenience stores attract armed robbers who are looking to rob a cashier for the money in the register (D’Alessio & StolzenBerg, 1990; Duffala, 1976; Exum, Kuhns, Koch, & Johnson, 2010). These studies have identified which types of stores pose the highest risk of victimization based on store accessibility and contextual factors so that crime prevention measures can be implemented.…”
Section: Commercial Facilities and Crimementioning
confidence: 99%
“…Informed by rational choice theory, SCP considers offenders as rational actors, comparing the costs and benefits of any particular criminal opportunity (Feeney 1986;Clarke 1997). Several evaluation and empirical studies have considered situational crime prevention strategies for convenience stores (Amandus et al 1995;Hendricks et al 1999;Exum et al 2010), liquor stores (Casteel et al 2004), and fast-food restaurants compared to convenience stores (Exum et al 2010) and found a reduction in associated crime rates.…”
Section: Crime Prevention Situational Crime Prevention and (Pharmacymentioning
confidence: 99%
“…Certain dispositional theories are best suited to study the motivations of offenders, as these theories focus on the psychological, biological, and sociological antecedents of criminal behaviour (Clarke, 1980). Situational theories are particularly appropriate for the study of crime prevention measures for commercial businesses, as situational crime prevention measures may be applied with a broad scope on the macro level, while utilizing crime-specific measures on a micro scale (Exum, Kuhns, Koch, & Johnson, 2010).…”
Section: Theory Integrationmentioning
confidence: 99%